2005
DOI: 10.1097/00000542-200512000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Labor Epidural Analgesia with and without Fentanyl on Infant Breast-feeding

Abstract: Among women who breast-fed previously, those who were randomly assigned to receive high-dose labor epidural fentanyl were more likely to have stopped breast-feeding 6 weeks postpartum than woman who were randomly assigned to receive less fentanyl or no fentanyl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
66
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(71 citation statements)
references
References 24 publications
2
66
1
2
Order By: Relevance
“…Intrapartum analgesia may also have an impact on breastfeeding, and consideration needs to be given to the type and dose of analgesia. 6,[21][22][23] Epidural analgesia, intramuscular opioids, exogenous oxytocin, and ergometrine have all been associated with lower rates of breastfeeding initiation. 24 (I, II-2, III)…”
Section: Prenatalmentioning
confidence: 99%
“…Intrapartum analgesia may also have an impact on breastfeeding, and consideration needs to be given to the type and dose of analgesia. 6,[21][22][23] Epidural analgesia, intramuscular opioids, exogenous oxytocin, and ergometrine have all been associated with lower rates of breastfeeding initiation. 24 (I, II-2, III)…”
Section: Prenatalmentioning
confidence: 99%
“…In a systematic review, Leighton and Halpern (2002) concluded that EDA does not affect breast-feeding initiation or management. The question of whether EDA would still be linked with breastfeeding failure was raised again when Beilin et al (2005) noted in a RCT that those women who received more than 150 µg of fentanyl in the EDA were less likely to continue breast-feeding at 6 weeks after delivery. In this respect, one could speculate that an ultra-short analgesic may have an advantage over longer acting medications.…”
Section: Effects Of Maternal Analgesia On the Neonatementioning
confidence: 99%
“…The newborns of women who receive certain kinds of epidurals (that include a narcotic drug) have more problems breastfeeding in the first hours, days, and weeks after birth (Beilin et al, 2005;Jordan, Emery, Bradshaw, Watkins, & Friswell, 2005;Lieberman & O'Donoghue, 2002;Radzyminski, 2003Radzyminski, , 2005Torvaldsen, Roberts, Simpson, Thompson, & Ellwood, 2006).…”
Section: Epidural Analgesiamentioning
confidence: 99%